In-situ template cooperated with thiourea to prepare oxygen/nitrogen co-doped porous carbons with adjustable pore structure for supercapacitors. (June 2020) - Zhou, Yuhao; Ren, Xue; Song, Mingyuan; Du, Yueyao; Wan, Jiafeng; Wu, Guang; Ma, Fangwei
Abstract: The exploration of preparing hierarchically porous carbons with adjustable pore structure from renewable biomass has attracted increasing attention by researchers. In this paper, the hierarchically porous carbon with excellent electrochemical properties is synthesized using renewable sodium alginate as a carbon source by in-situ pyrolysis of 'egg-box' structure with the addition of thiourea. The type/concentration of template resources and the thiourea additive have an important influence on the regulation of pore structure and the content of heteroatom here. More importantly, the doping of graphitic-N is conducive to enhancing the cycle stability of the electrode material. The PCNS–Zn sample has the most outstanding electrochemical performance with the high specific capacitance of 350 F g −1 at 1 A g −1 and the good rate capability of 82% capacitance retention at 50 A g −1 . In addition, PCNS–Zn electrode shows a prominent cycle life with the capacitance retention rate of 90.4% at 5 A g −1 after 5000 cycles. From the perspective of sustainability, low cost and easy operation, this scheme has a broad development prospect for preparing porous carbon with controllable pore structure. Highlights: Porous carbons have been prepared by assembling of alginate and divalent cationic. The template sources have an influence on the pore structure and nitrogen species. Thiourea could regulate the size of template nano particles. The doping of graphitic-N is conducive to enhance the cycle stability.